Effects of Gintonin-enriched fraction on the gene expression of six lysophosphatidic receptor subtypes - Lee, Rami; Lee, Byung-Hwan; Choi, Sun-Hye; Cho, Yeon-Jin; Cho, Han-Sung; Kim, Hyoung-Chun; Rhim, Hyewhon; Cho, Ik-Hyun; Rhee, Man Hee; Nah, Seung-Yeol (고려인삼학회, 2021)
Background: Gintonin, isolated from ginseng, acts as a ginseng-derived lysophosphatidic acid (LPA) receptor ligand and elicits the [Ca2+], transient through six LPA receptor subtypes (LPARSs). However, the long-term effects of gintonin-enriched fraction (GEF) on the gene expression of six LPARSs remain unknown. We examined changes in the gene expression of six LPA receptors in the mouse whole brain, heart, lungs, liver, kidneys, spleen, small intestine, colon, and testis after long-term oral GEF administration. Methods: C57BL/6 mice were divided into two groups: control vehicle and GEF (100 mg/kg, p.o.). After 21-day saline or GEF treatment, total RNA was extracted from nine mouse organs. Quantitative-real-time PCR (qRT-PCR) and western blot were performed to quantify changes in the gene and protein expression of the six LPARSs, respectively. Results: qRT-PCR analysis before GEF treatment revealed that the LPA6 RS was predominant in all organs except the small intestine. The LPA2 RS was most abundant in the small intestine. Long-term GEF administration differentially regulated the six LPARSs. Upon GEF treatment, the LPA6 RS significantly increased in the liver, small intestine, colon, and testis but decreased in the whole brain, heart, lungs, and kidneys. Western blot analysis of the LPA6 RS confirmed the differential effects of GEF on LPA6 receptor protein levels in the whole brain, liver, small intestine, and testis. Conclusion: The LPA6 receptor was predominantly expressed in all nine organs examined; long-term oral GEF administration differentially regulated LPA3, LPA4, and LPA6 receptors in the whole brain, heart, lungs, liver, kidneys, small intestine, and testis. (C) 2021 The Korean Society of Ginseng. Publishing services by Elsevier B.V.